Advances in the genetics of schizophrenia: toward a network and pathway view for drug discovery - Collier, David A.; Eastwood, Brian J.; Malki, Karim; Mokrab, Younes (Annals of the New York Academy of Sciences, 2016)
The spectacular advance in our understanding of the genetic basis of schizophrenia through genome‐wide association studies has the potential to identify new leads for drug treatment through improved understanding of disease pathophysiology. However, using these genetic associations successfully in drug development and patient stratification requires further target validation, particularly in understanding which gene(s) is causal in the disease, how the risk variants alter gene function and regulation, and how they fit into disease pathways and networks. If researchers consider the disease network as the target, they need to understand which genes should be targeted and in which modality, in order to modulate pathophysiology and obtain a beneficial effect for the patient. In the present article, we review recent genetic findings in schizophrenia and discuss how these might be validated with biology and integrated with epigenetic and transcriptome data to identify targets that lie within disease networks and pathways. This new understanding of disease biology will also facilitate the development of assays that recapitulate specific aspects of the disease using model organisms and cells. These assays can then be used in screening approaches, which manipulate disease networks or pathological processes to generate and test therapeutic strategies.